Molecular cloning, sequencing and tissue expression of vasotocin and isotocin precursor genes from Ostariophysian catfishes: phylogeny and evolutionary considerations in teleosts - Banerjee, Putul; Chaube, Radha; Joy, Keerikkattil P. (Frontiers in Neuroscience, 2015)
Basic and neutral neurohypophyseal (NH) nonapeptides have evolved from vasotocin (VT) by a gene duplication at the base of the gnathostome lineage. In teleosts, VT and IT are the basic and neutral peptides, respectively. In the present study, VT and IT precursor genes of Heteropneustes fossilis and Clarias batrachus (Siluriformes, Ostariophysi) were cloned and sequenced. The channel catfish Icatalurus punctatus NH precursor sequences were obtained from EST database. The catfish NH sequences were used along with the available Acanthopterygii and other vertebrate NH precursor sequences to draw phylogenetic inference on the evolutionary history of the teleost NH peptides. Synteny analysis of the NH gene loci in various teleost species was done to complement the phylogenetic analysis. In H. fossilis, the NH transcripts were also sequenced from the ovary. The cloned genes and the deduced precursor proteins showed conserved characteristics of the NH nonapeptide precursors. The genes are expressed in brain and ovary (follicular envelope) of H. fossilis with higher transcript abundance in the brain. The addition of the catfish sequences in the phylogenetic analysis revealed that the VT and IT precursors of the species-rich superorders of teleosts have a distinct phylogenetic history with the Acanthopterygii VT and IT precursors sharing a less evolutionary distance and the Ostariophysi VT and IT having a greater evolutionary distance. The genomic location of VT and IT precursors, and synteny analysis of the NH loci lend support to the phylogenetic inference and suggest a footprint of fish- specific whole genome duplication (3R) and subsequent diploidization in the NH loci. The VT and IT precursor genes are most likely lineage-specific paralogs resulting from differential losses of the 3R NH paralogs in the two superorders. The independent yet consistent retention of VT and IT in the two superorders might be directed by a stringent ligand-receptor selectivity.